2011
DOI: 10.1088/0004-6256/142/4/106
|View full text |Cite
|
Sign up to set email alerts
|

V405 Andromeda Revisited

Abstract: We present a multi-epoch time-resolved high-resolution optical spectroscopy study of the short-period (P orb = 11.2 hr) eclipsing M0V+M5V RS CVn binary V405 Andromeda. By means of indirect imaging techniques, namely Doppler imaging, we study the surface activity features of the M0V component of the system. A modified version of a Doppler imaging code, which takes into account the tidal distortion of the surface of the star, is applied to the multi-epoch data set in order to provide indirect images of the stell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Strong flares in the light curve and the Hα region were observed, and by modeling the system they showed that the radius of the primary was significantly larger than the theoretically predicted value, while the size of the secondary fit the mass-radius relation. This result was later confirmed by Ribeiro, Baptista & Kafka (2011) who used an independent spectroscopy-based method to determine the size of the components.…”
Section: Introductionmentioning
confidence: 71%
“…Strong flares in the light curve and the Hα region were observed, and by modeling the system they showed that the radius of the primary was significantly larger than the theoretically predicted value, while the size of the secondary fit the mass-radius relation. This result was later confirmed by Ribeiro, Baptista & Kafka (2011) who used an independent spectroscopy-based method to determine the size of the components.…”
Section: Introductionmentioning
confidence: 71%
“…However, the problem appears to be exacerbated by more well-studied systems, which exhibit near-10% radius discrepancies (Popper 1997;Feiden & Chaboyer 2012a;Terrien et al 2012). To further complicate the matter, seemingly hyper-inflated stars show radii inflated by more than 50% (Vida et al 2009;C ¸akırlı et al 2010;Ribeiro et al 2011;C ¸akırlı et al 2013a,b). Whether the mechanism puffing up the hyper-inflated stars is related to the more common sub-10% inflation is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Strong flares in the light curve and the Hα region were observed, and by modeling the system they showed that the radius of the primary was significantly larger than the theoretically predicted value, while the size of the secondary fit the mass-radius relation. This result was later confirmed by Ribeiro, Baptista, & Kafka (2011), who used an independent spectroscopy-based method to determine the size of the components. GSC 3377-0296 was studied to date only by Lloyd et al (2007), who identified the object as a heavily spotted RS CVn system with an orbital period of 0.422 days.…”
Section: Introductionmentioning
confidence: 72%